Jatropha tanjorensis Euphorbiaceae ameliorates aspirin-induced hepatotoxicity and maintain electrolytes balance in albino Wistar rats - Elizabeth B. Umoren; Idara A. Okon; Emmanuel U. Modo; Okon E. Etim; Providence I. Brown; Daniel U. Owu; Augustine I.L. Bassey (Elsevier, 2023)
Background: A great number of modern medicines derived from plants are considered as important sources of medicinal agents to treat different diseases. J. tanjorensis belongs to the family Euphorbiaceae, which is known for various medicinal uses. Purpose: The hepatoprotective effect of ethanolic extract of J. tanjorensis Euphorbiaceae and maintenance of electrolytes balance in aspirin-induced hepatotoxic condition in Wistar rats was studied. Methods: 20 Wistar rats of both sexes weighing between (180-200 g) were divided into 4 groups of 5 rats each.  normal rat (group 1); J. tanjorensis Euphorbiaceae (200 mg/kg group 2); aspirin (250 mg/kg group 3); aspirin (250 mg/kg) + J. tanjorensis Euphorbiaceae (200 mg/kg group 4). Serum levels of the enzymes aspartate transaminase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), and electrolytes (Na+, K+, Cl−, and HCO3−) was assessed at the end of treatment which lasted twelve (12) weeks. Results: When compared to control, J. tanjorensis Euphorbiaceae - treated, and aspirin+ J. tanjorensis Euphorbiaceae - treated groups, blood electrolyte results in aspirin-treated group indicated a significant decrease (p<0.05) in sodium, potassium, chloride, and bicarbonate levels, respectively. Treatment with J. tanjorensis Euphorbiaceae leaves extract resulted in normal levels of serum electrolytes (Na+, Cl−, and HCO3−). When compared to J. tanjorensis Euphorbiaceae, control, and aspirin + J. tanjorensis Euphorbiaceae -treated groups, the serum liver enzyme level was significantly (p<0.05) increased in the aspirin-treated group. When compared to the aspirin treated group, serum liver enzymes level in the J. tanjorensis Euphorbiaceae treated group was significantly lower (p<0.05). The relative liver weight and mean body weight in the aspirin-treated group was significantly lower (p<0.05) compared to J. tanjorensis Euphorbiaceae, control, and aspirin + J. tanjorensis Euphorbiaceae - treated groups respectively. Conclusion: The results suggest ethanolic leaves extract of J. tanjorensis Euphorbiaceae offered hepato-protective effect in aspirin-induced hepatotoxic condition on tissues, ameliorated both hyponatriemia and hyperkalemia effects,  and maintained normal electrolytes concentration in animal models.